Timing and Spectral studies of SXP 15.3 near its Eddington luminosity - Maitra, Chandreyee; Paul, Biswajit; Haberl, Frank; Vasilopoulos, Georgios; Sreenandini, Anand T. S. (2018)
SXP 15.3 (RX J0052.1-7319) is a Be X-ray binary pulsar located in the Small Magellanic Cloud. The source was classified as a transient X-ray binary candidate based on ROSAT observations in the 1990's, and pulsations at 15.3 s were subsequently discovered from an outburst in 1996 from the ROSAT data. The source has never been studied in an outburst or a bright state ever since. Following reports of an outburst in November 2017, we triggered a Target of Opportunity observation of SXP 15.3 with AstroSat. We report here the first broadband spectral and timing studies of the source, when the source was accreting near the Eddington limit of 10^38 erg/s. We discuss the energy dependence of the pulse profiles and the broadband spectrum in context of accretion onto magnetized neutron stars accreting near its Eddington limit.